Production process for reducing magnetic substance content of artificial graphite negative electrode material and artificial graphite negative electrode material thereof
By in the production process of artificial graphite negative materials, graphization and multi -layered magnetic selection in the high temperature inert atmosphere solve the problem of high magnetic objects in existing technology, realize low -cost, efficient magnetic removal, improved, and improved the improvement, which has been improved. The purity and performance of the material.
Patent Information
- Application Number
- CN202411511263.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-28
AI Technical Summary
In the existing artificial graphite negative electrode material production process, the magnetic content is high, resulting in a decrease in electrochemical performance and increased safety risks, and multiple magnetic separations increase energy consumption and production costs.
Graphize at a temperature of 2800 ° C and above in the inert atmosphere, gasification magnetic substances, and relying on the combination, mixed batch, screening, and magnetic selection before carbonization. Materials, reduce magnetic objects.
You can obtain artificial graphite negative materials with magnetic objects lower than 3PPM without multiple magnetic selections, reducing production costs and energy consumption, and improving the purity and electrochemical properties of the material.
Smart Images

Figure CN119370839A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery negative electrode material preparation, in particular to a production process for reducing the magnetic substance content of artificial graphite negative electrode materials and the artificial graphite negative electrode materials. Background Art
[0002] Magnetic substances, such as iron and nickel, can exist in the graphite of the negative electrode of lithium batteries, and they may affect the performance of lithium batteries. Specifically, it manifests in: ① Affecting the electrochemical performance of the battery: The presence of magnetic substances may change the electrochemical properties of the graphite surface, resulting in a decrease in the energy density of the battery and a slowdown in the electrochemical reaction rate, thereby affecting its performance. ② Affecting the safety of the battery: Lithium batteries will induce thermal effects during the charging and discharging process, and the presence of magnetic substances may promote the heating of the battery, further causing safety issues for the battery. In the production process of existing artificial graphite negative electrode materials, magnetic separation is usually carried out after carbonization. The carbonized material has a high content of magnetic substances, and it is usually necessary to carry out multiple magnetic separations to obtain artificial graphite negative electrode products with a low content of magnetic substances. At the same time, the presence of magnetic substances will increase the energy consumption in processes such as carbonization, which is not conducive to reducing the production cost of artificial graphite negative electrode materials.
[0003] Therefore, there is an urgent need for a production process that reduces the magnetic content of artificial graphite negative electrode materials to solve the shortcomings of the prior art. Summary of the invention
[0004] The object of the present invention is to provide a production process for reducing the magnetic content of artificial graphite negative electrode materials and artificial graphite negative electrode materials. The production process of the present invention is simple and easy, and artificial graphite negative electrode materials with a magnetic content of less than 3ppm can be obtained without multiple magnetic separations.
[0005] To achieve the above object, the present invention provides, on one hand, a production process for reducing the magnetic content of artificial graphite negative electrode materials, comprising the steps of:
[0006] (1) graphitizing an artificial graphite precursor in an inert atmosphere to obtain a graphitized product, wherein the graphitization temperature is 2800° C. or above;
[0007] (2) depolymerizing, batch mixing and screening the graphitized product to obtain graphitized particles;
[0008] (3) The graphitized particles are sequentially subjected to magnetic separation in a first demagnetizer and a second demagnetizer to obtain demagnetized material, wherein the magnetic induction intensity of the first demagnetizer and the second demagnetizer is greater than the magnetic induction intensity of the magnetic object detection and the magnetic induction intensity of the first demagnetizer is less than the magnetic induction intensity of the second demagnetizer;
[0009] (4) kneading the demagnetizing material and the binder and then carbonizing them to obtain a carbonized material;
[0010] (5) The carbonized material is subjected to secondary screening to obtain an artificial graphite negative electrode material.
[0011] Compared with the prior art, the present invention can gasify magnetic substances such as iron, chromium, nickel, zinc, copper, and cobalt in the artificial graphite precursor by graphitizing the artificial graphite precursor under an inert atmosphere and a temperature of 2800°C or above, and can effectively prevent the magnetic substances from reacting with oxygen to generate other impurities, thereby improving the purity of the artificial graphite and reducing the influence of excessive magnetic content on subsequent electrochemical performance. In addition, the present invention depolymerizes, batches, screens, and magnetically separates the graphitized product before carbonization, which can effectively prevent the artificial graphite precursor from being completely gasified during the graphitization process due to the fact that some magnetic substances are wrapped inside the graphitized product, and the magnetic content increases due to the fact that the magnetic substances change from weak magnetic to strong magnetic due to the influence of factors such as oxygen during the carbonization process. In the present invention, by setting the magnetic induction intensity of the first demagnetizer and the second demagnetizer to be greater than the magnetic induction intensity of the magnetic object detection, the weak magnetism that cannot be removed during the magnetic object detection can be effectively removed, and the magnetic induction intensity of the first demagnetizer is further made smaller than the magnetic induction intensity of the second demagnetizer, so that magnetic objects with different magnetic strengths can be effectively removed in layers, thereby improving the magnetic separation efficiency. Therefore, the production process of the present invention can effectively reduce the magnetic content of artificial graphite negative electrode materials, and artificial graphite negative electrode materials with a magnetic content of less than 3ppm can be obtained without multiple magnetic separations.
[0012] In some embodiments, the artificial graphite precursor is selected from at least one of anthracite, needle coke, petroleum coke and asphalt, and the magnetic substance in the artificial graphite precursor includes at least one of iron, chromium, nickel, zinc, copper and cobalt.
[0013] In some embodiments, the inert atmosphere is selected from at least one of nitrogen, helium and argon, the graphitization temperature is 2800° C. to 3100° C., and the time is 45 h to 58 h.
[0014] In some embodiments, depolymerization is carried out in a crusher, the rotation speed of the crusher is 900r / min~1400r / min, the particle size of the graphitized product after depolymerization is 0.002mm~5mm and 95% and above can pass through a 325-mesh sieve, and batch mixing is carried out in a batch mixer, the batch mixing time is 60min~120min, the rotation speed of the batch mixer is 150r / min~300r / min, and the screening mesh number used for screening is 200 mesh~500 mesh.
[0015] In some embodiments, the magnetic field strength for detecting magnetic objects is 6000 to 7000 gauss, the magnetic induction strength of the first demagnetizer is 15,000 to 20,000 gauss, and the magnetic induction strength of the second demagnetizer is 25,000 to 30,000 gauss.
[0016] In some embodiments, the demagnetization time of the first demagnetizer and the demagnetization time of the second demagnetizer are each independently 60s to 150s, the feeding time of the first demagnetizer and the feeding time of the second demagnetizer are each independently 200s to 500s, and the slag discharge time of the first demagnetizer and the slag discharge time of the second demagnetizer are each independently 200s to 500s.
[0017] In some embodiments, the binder is selected from at least one of asphalt and resin, and the kneading is carried out in a kneader. The kneading temperature is 20°C to 40°C, the time is 90min to 150min, the rotation speed of the kneader is 100r / min to 300r / min, the carbonization temperature is 1100°C to 1200°C, the heating rate is 2°C / min to 3°C / min, and the insulation time is 5h-8h.
[0018] In some embodiments, in step (4), after carbonization, deagglomeration, batch mixing, screening and magnetic separation are sequentially included.
[0019] In some embodiments, the secondary screening uses a screening mesh of 200-500 mesh.
[0020] On the other hand, the present invention provides an artificial graphite negative electrode material, which is produced by the above-mentioned production process, and the magnetic content of the obtained artificial graphite negative electrode material is less than or equal to 3ppm. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic diagram of the change of magnetic content of graphitized products and carbonized products;
[0022] Figure 2 This is a schematic diagram of a process flow of a production process for reducing the magnetic substance content of an artificial graphite negative electrode material according to Example 1 of the present invention;
[0023] Figure 3 This is a process flow diagram of a production process for reducing the magnetic substance content of artificial graphite negative electrode materials according to Example 4 of the present invention;
[0024] Figure 4 This is a schematic diagram of the process flow of the production process for reducing the magnetic content of artificial graphite negative electrode materials in comparative example 1 of the present invention. DETAILED DESCRIPTION
[0025] In the process of preparing artificial graphite negative electrode materials, the applicant found in the research process that the content of magnetic substances in the graphitized product obtained after graphitization of the artificial graphite precursor is low, but the content of magnetic substances in the graphitized product after carbonization shows a trend of increasing. For details, please refer to Figure 1The graphite product in the figure is a schematic diagram of the change in magnetic content after carbonization. From the magnetic content data of the graphite product and carbonized product in batches D, E, and F in the figure, it can be seen that the magnetic content after carbonization shows a significant increase trend. Based on the above problems encountered in production, the present invention provides a production process for reducing the magnetic content of artificial graphite negative electrode materials, through which artificial graphite negative electrode materials with a magnetic content of less than 3ppm can be obtained without multiple magnetic separations.
[0026] For details, please see Figure 2 A production process for reducing the magnetic content of artificial graphite negative electrode materials of the present invention comprises the steps of:
[0027] (1) graphitizing an artificial graphite precursor in an inert atmosphere to obtain a graphitized product;
[0028] (2) depolymerizing, batch mixing and screening the graphitized product to obtain graphitized particles;
[0029] (3) subjecting the graphitized particles to magnetic separation in a first demagnetizer and a second demagnetizer in sequence to obtain demagnetized material;
[0030] (4) kneading the demagnetizing material and the binder and carbonizing them to obtain a carbonized material;
[0031] (5) The carbonized material is subjected to secondary screening to obtain an artificial graphite negative electrode material.
[0032] In step (1), the artificial graphite precursor is selected from at least one of anthracite, needle coke, petroleum coke and asphalt. The magnetic material in the artificial graphite precursor includes at least one of iron, chromium, nickel, zinc, copper and cobalt. The graphitization temperature is 2800°C and above. In some technical schemes, the graphitization temperature is 2800°C to 3100°C. As an example, the graphitization temperature can be but not limited to 2800°C, 2850°C, 2900°C, 2950°C, 3000°C, 3050°C, 3100°C. The graphitization time is 45h to 58h. In some technical schemes, the graphitization time is 48h to 56h. As an example, the graphitization time can be but not limited to 45h, 46h, 47h, 48h, 49h, 50h, 52h, 54h, 56h, 58h. The inert atmosphere is selected from at least one of nitrogen, argon and helium.
[0033] Since the artificial graphite precursor contains magnetic substances such as iron, chromium, nickel, zinc, copper, and cobalt, the presence of magnetic substances will affect the electrochemical performance of the artificial graphite negative electrode material in the secondary battery, so it is necessary to effectively remove such substances. Magnetic substances such as iron, chromium, nickel, zinc, copper, and cobalt will gasify under the condition of reaching a certain temperature. For example, the gasification temperature of iron is 2750°C, the gasification temperature of chromium is 2672°C, the gasification temperature of nickel is 2732°C, the gasification temperature of zinc is 906°C, the gasification temperature of copper is 2562°C, and the gasification temperature of cobalt is 2870°C. Therefore, the present invention graphitizes the artificial graphite precursor by controlling the graphitization temperature to be above 2800°C, and at the same time, the magnetic substances contained in the graphite precursor, such as iron, chromium, nickel, zinc, copper, and cobalt, can be gasified at this temperature, thereby reducing the content of magnetic substances in the graphitized product, and effectively avoiding the influence of the excessive content of magnetic substances in the artificial graphite negative electrode material on the electrochemical performance. At the same time, graphitization in an inert atmosphere can effectively avoid the formation of metal oxide impurities when reacting with oxygen under high temperature conditions, thereby improving the purity of artificial graphite.
[0034] In step (2), depolymerization, mixed batching and screening are performed before magnetic separation to obtain graphitized particles to improve the subsequent magnetic separation efficiency. Since the graphitized precursor is subjected to a high temperature of 2800°C or above, some graphitized products are bonded, agglomerated and agglomerated, and the bonded particles are hard and the agglomerates are large, so depolymerization treatment is required first. Depolymerization can be carried out in a crusher, and the speed of the crusher is 900r / min to 1400r / min. In some technical solutions, the speed of the crusher is 980r / min to 1250r / min. As an example, the speed of the crusher can be but is not limited to 900r / min, 950r / min, 1000r / min, 1050r / min, 1100r / min, 1150r / min, 1200r / min, 1250r / min, 1300r / min, 1350r / min, 1400r / min. In some technical solutions, the crusher may be a toothed roller crusher. The toothed roller crusher is mainly composed of a motor, a reducer, a transmission device, a frame part, a crushing tooth linkage mechanism, etc. Its working principle is to split, crush and depolymerize the material through the high-speed rotation of a special wear-resistant toothed roller. The present invention does not limit the model of the toothed roller crusher, and it can be any type of toothed roller crusher in the prior art. The particle size of the graphitized product after depolymerization is 0.002mm to 5mm, and 95% or more of the graphitized products can pass through a 325-mesh sieve. As an example, the particle size of the graphitized product after depolymerization can be, but is not limited to, 0.002mm, 0.008mm, 0.01mm, 0.05mm, 0.1mm, 0.5mm, 1mm, 1.5mm, 2mm, 2.5mm, 3mm, 3.5mm, 4mm, 4.5mm, 5mm.
[0035] The depolymerized graphite products are mixed in batches to improve the consistency of the graphite product particle size, reduce the extreme difference in the physical and chemical indicators of the graphite products, and reduce the process adjustment during the subsequent magnetic separation work to improve the magnetic separation efficiency. The mixed batches can be carried out in a batch mixer. The batch mixer can be a screw belt batch mixer, and the volume of the batch mixer can be 10m 3 、15m 3 、20m 3 or 30m 3 , the larger the volume of the batch mixer, the more consistent the uniformity of the single batch mixing. The batch mixing time is 60min to 120min. In some technical solutions, the batch mixing time is 75min to 108min. As an example, the batch mixing time can be but not limited to 60min, 70min, 80min, 90min, 100min, 110min, 120min. The speed of the batch mixer is 150r / min to 300r / min. In some technical solutions, the speed of the batch mixer is 180r / min to 275r / min. As an example, the speed of the batch mixer is 150r / min, 180r / min, 200r / min, 220r / min, 240r / min, 260r / min, 280r / min, 300r / min.
[0036] The mixed batch of graphitized products is screened, and the screened product is taken to obtain graphitized particles. The screen mesh number used for screening is 200-500 mesh. In some technical solutions, the screen mesh number used for screening is 225-465 mesh. In some technical solutions, the screen mesh number used for screening is 325 mesh. As an example, the screen mesh number can be but not limited to 200 mesh, 250 mesh, 300 mesh, 350 mesh, 400 mesh, 450 mesh,
[0037] 500 mesh. The graphitized products are separated by the aperture of the screen to remove large particles and impurities and obtain more uniform material particles. It is beneficial to better remove magnetic particles during magnetic separation. Ultrasonic vibrating screens can be used for screening. Screening can ensure that the particle size of the magnetic separation product flowing into the next process meets the requirements; and large particles and agglomerated small particles can be removed. Since magnetic metal materials are easily coated in large particles and agglomerated small particles, screening this part improves the efficiency and yield of magnetic separation. The particle size D50 of the graphitized particles is 4μm to 20μm. In some technical schemes, the particle size D50 of the graphitized particles is 5μm to 16μm. As an example, the particle size D50 of the graphitized particles can be but is not limited to 4μm, 6μm, 8μm, 10μm,
[0038] 12μm, 14μm, 16μm, 18μm, 20μm.
[0039] In step (3), the magnetic field generated by the demagnetizer is used to remove the magnetic substances and impurities in the graphitized particles to meet the stability of battery material processing. The demagnetizer of the present invention includes a first demagnetizer and a second demagnetizer, and the magnetic induction intensity of the first demagnetizer and the second demagnetizer are both greater than the magnetic induction intensity of the magnetic object detection, and the magnetic induction intensity of the first demagnetizer is less than the magnetic induction intensity of the second demagnetizer. The graphitized particles are first magnetically separated in the first demagnetizer, so that most of the magnetic substances can be removed, and then enter the second demagnetizer with higher magnetic induction intensity, which can effectively remove the remaining part and the weaker magnetic substances, thereby enhancing the working efficiency of the magnetic separation. The magnetic field intensity of the magnetic object detection is 6000 Gauss to 7000 Gauss. In some technical solutions, the magnetic field intensity of the magnetic object detection is 6000 Gauss. As an example, the magnetic field intensity of the magnetic object detection can be, but is not limited to, 6000 Gauss, 6200 Gauss, 6400 Gauss, 6600 Gauss, 6800 Gauss, and 7000 Gauss. The magnetic induction intensity of the first demagnetizer is 15,000 to 20,000 gauss. In some technical solutions, the magnetic field intensity of the first demagnetizer is 20,000 gauss. As an example, the magnetic field intensity of the first demagnetizer can be, but not limited to, 15,000 gauss, 16,000 gauss, 17,000 gauss, 18,000 gauss, 19,000 gauss, and 20,000 gauss. The magnetic induction intensity of the second demagnetizer is 25,000 to 30,000 gauss. In some technical solutions, the magnetic field intensity of the second demagnetizer is 30,000 gauss. As an example, the magnetic field intensity of the second demagnetizer can be, but not limited to, 25,000 gauss, 26,000 gauss, 27,000 gauss, 28,000 gauss, 29,000 gauss, and 30,000 gauss. The demagnetization time of the first demagnetizer and the demagnetization time of the second demagnetizer are each independently 60s to 150s. As an example, the demagnetization time of the first demagnetizer can be, but is not limited to, 60s, 70s, 80s, 90s, 100s, 110s, 120s, 130s, 140s, and 150s. As an example, the demagnetization time of the second demagnetizer can be, but is not limited to, 60s, 70s, 80s, 90s, 100s, 110s, 120s, 130s, 140s, and 150s. The feeding time of the first demagnetizer and the feeding time of the second demagnetizer are each independently 200s to 500s. As an example, the feeding time of the first demagnetizer can be, but is not limited to, 200s, 250s, 300s, 350s, 400s, 450s, and 500s. As an example, the feeding time of the second demagnetizer can be, but is not limited to, 200s, 250s, 300s, 350s, 400s, 450s, 500s. The slag discharge time of the first demagnetizer and the slag discharge time of the second demagnetizer are each independently 200s to 500s. As an example, the slag discharge time of the first demagnetizer can be, but is not limited to, 200s, 250s, 300s, 350s, 400s, 450s, 500s.As an example, the slag discharge time of the second demagnetizer can be but is not limited to 200s, 250s, 300s, 350s, 400s, 450s, and 500s.
[0040] In step (4), the binder is selected from at least one of asphalt and resin. Kneading can be specifically carried out in a kneader. The kneading temperature is 20°C to 40°C. As an example, the kneading temperature can be, but is not limited to, 20°C, 22°C, 24°C, 26°C, 28°C, 30°C, 32°C, 34°C, 36°C, 38°C, 40°C. The kneading time is 90min to 150min. In some technical solutions, the kneading time is 105min to 135min. As an example, the kneading time can be, but is not limited to, 90min, 95min, 100min, 105min, 110min, 115min, 120min, 125min, 130min, 135min, 140min, 145min, 150min. The speed of the kneader is 100r / min to 300r / min. In some technical solutions, the speed of the kneading machine is 180 r / min to 250 r / min. As an example, the speed of the kneading machine can be, but is not limited to, 100 r / min, 120 r / min, 140 r / min, 160 r / min, 180 r / min, 200 r / min, 220 r / min, 240 r / min, 260 r / min, 280 r / min, and 300 r / min.
[0041] Carbonization adopts at least one of a roller furnace, a tunnel furnace, and a box-type fixed furnace. The temperature of carbonization is 1100°C to 1200°C. As an example, the temperature of carbonization can be, but is not limited to, 1100°C, 1110°C, 1120°C, 1130°C, 1140°C, 1150°C, 1160°C, 1170°C, 1180°C, 1190°C, and 1200°C. The heating rate is 2°C / min to 3°C / min. As an example, the heating rate can be, but is not limited to, 2°C / min, 2.1°C / min, 2.2°C / min, 2.3°C / min, 2.4°C / min, 2.5°C / min, 2.6°C / min, 2.7°C / min, 2.8°C / min, 2.9°C / min, and 3°C / min. The insulation time is 5h to 8h. As an example, the insulation time can be, but is not limited to, 5h, 6h, 7h, and 8h.
[0042] In step (5), the mesh size of the secondary screening is 200-500 mesh. In some technical solutions, the mesh size of the secondary screening is 325 mesh. As an example, the mesh size of the secondary screening can be, but is not limited to, 200 mesh, 250 mesh, 300 mesh, 350 mesh, 400 mesh, 450 mesh, and 500 mesh.
[0043] Then by Figure 3 As shown, in step (4), after carbonization, deagglomeration, batch mixing, screening and magnetic separation are sequentially included. The deagglomeration, batch mixing, screening and magnetic separation may be the same as or different from the deagglomeration, batch mixing, screening and magnetic separation in steps (2) and (3). Deagglomeration, batch mixing, screening and magnetic separation after carbonization can further reduce the magnetic content, thereby obtaining artificial graphite negative electrode materials with lower magnetic content to meet the different needs of different products.
[0044] Specifically, the primary depolymerization can be carried out in a crusher, and the rotation speed of the crusher is 900r / min to 1400r / min. In some technical solutions, the rotation speed of the crusher is 950r / min to 1350r / min. In some technical solutions, the rotation speed of the crusher is 1050r / min to 1260r / min. As an example, the rotation speed of the crusher can be but is not limited to 900r / min, 950r / min, 1000r / min, 1050r / min, 1100r / min, 1150r / min, 1200r / min, 1250r / min, 1300r / min, 1350r / min, 1400r / min. In some technical solutions, the crusher can be a toothed roller crusher. The particle size of the material after the primary depolymerization is 0.002mm to 5mm and 95% or more of the graphitized products can pass through a 325 mesh sieve. In some technical schemes, the particle size of the material after one depolymerization is 0.002mm~3mm. In some technical schemes, the particle size of the material after one depolymerization is 0.01mm~1mm. As an example, the particle size of the material after one depolymerization can be but is not limited to 0.002mm, 0.008mm, 0.01mm, 0.05mm, 0.1mm, 0.5mm, 1mm, 1.5mm, 2mm, 2.5mm, 3mm, 3.5mm, 4mm, 4.5mm, and 5mm.
[0045] A mixed batch can be carried out in a mixed batch machine. The time for a mixed batch is 60min to 120min. In some technical solutions, the time for a mixed batch is 78min to 110min. In some technical solutions, the time for a mixed batch is 85min to 100min. As an example, the time for a mixed batch can be but is not limited to 60min, 70min, 80min, 90min, 100min, 110min, 120min. The speed of the mixed batch machine is 150r / min to 300r / min. In some technical solutions, the speed of the mixed batch machine is 165r / min to 285r / min. In some technical solutions, the speed of the mixed batch machine is 180r / min to 220r / min. As an example, the speed of the mixed batch machine is 150r / min, 180r / min, 200r / min, 220r / min, 240r / min, 260r / min, 280r / min, 300r / min.
[0046] The sieving mesh number used for the first screening is 200 mesh to 500 mesh. In some technical schemes, the sieving mesh number used for the first screening is 205 mesh to 385 mesh. In some technical schemes, the sieving mesh number used for the first screening is 325 mesh. As an example, the mesh number of the first screening can be but is not limited to 200 mesh, 250 mesh, 300 mesh, 350 mesh, 400 mesh, 450 mesh, and 500 mesh.
[0047] A magnetic separation is carried out in at least one demagnetizer. In some technical solutions, the material is sequentially carried out in the first demagnetizer and the second demagnetizer. The magnetic induction intensity of the first demagnetizer can be 15,000 gauss to 20,000 gauss. In some technical solutions, the magnetic field intensity of the first demagnetizer is 20,000 gauss. As an example, the magnetic field intensity of the first demagnetizer can be, but not limited to, 15,000 gauss, 16,000 gauss, 17,000 gauss, 18,000 gauss, 19,000 gauss, and 20,000 gauss. The magnetic induction intensity of the second demagnetizer can be 25,000 gauss to 30,000 gauss. In some technical solutions, the magnetic field intensity of the second demagnetizer is 30,000 gauss. As an example, the magnetic field intensity of the second demagnetizer can be, but not limited to, 25,000 gauss, 26,000 gauss, 27,000 gauss, 28,000 gauss, 29,000 gauss, and 30,000 gauss. The demagnetization time of the first demagnetizer and the demagnetization time of the second demagnetizer are each independently 60s to 150s. As an example, the demagnetization time of the first demagnetizer can be, but is not limited to, 60s, 70s, 80s, 90s, 100s, 110s, 120s, 130s, 140s, and 150s. As an example, the demagnetization time of the second demagnetizer can be, but is not limited to, 60s, 70s, 80s, 90s, 100s, 110s, 120s, 130s, 140s, and 150s. The feeding time of the first demagnetizer and the feeding time of the second demagnetizer are each independently 200s to 500s. As an example, the feeding time of the first demagnetizer can be, but is not limited to, 200s, 250s, 300s, 350s, 400s, 450s, and 500s. As an example, the feeding time of the second demagnetizer may be, but is not limited to, 200s, 250s, 300s, 350s, 400s, 450s, and 500s. The slag discharge time of the first demagnetizer and the slag discharge time of the second demagnetizer are each independently 200s to 500s. As an example, the slag discharge time of the first demagnetizer may be, but is not limited to, 200s, 250s, 300s, 350s, 400s, 450s, and 500s. As an example, the slag discharge time of the second demagnetizer may be, but is not limited to, 200s, 250s, 300s, 350s, 400s, 450s, and 500s.
[0048] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.
[0049] Example 1
[0050] like Figure 1 As shown, this embodiment is a production process for reducing the magnetic content of artificial graphite negative electrode materials, including the steps of:
[0051] (1) graphitizing needle coke in a nitrogen atmosphere to obtain a graphitized product at a graphitization temperature of 2850° C. for 45 h;
[0052] (2) The graphitized product is first deagglomerated in a toothed roller crusher to a particle size of ≤3.5 mm, and then mixed in a batch mixer and sieved to obtain graphitized particles, wherein the speed of the batch mixer is 220 r / min, the mixing time is 80 min, the mesh number used for sieving is 325 mesh, and the particle size D50 of the graphitized particles is 14±2.0 μm;
[0053] (3) The graphitized particles are sequentially subjected to magnetic separation in a first demagnetizer and a second demagnetizer to obtain demagnetized material, wherein the magnetic induction intensity of the first demagnetizer is 20,000 Gauss, and the demagnetization time is 120 seconds; the magnetic induction intensity of the second demagnetizer is 30,000 Gauss, and the magnetic separation time is 120 seconds;
[0054] (4) kneading the demagnetized material and asphalt in a kneader and then carbonizing them in a tunnel furnace to obtain a carbonized material, wherein the kneading temperature is 20° C., the time is 80 min, the speed of the kneader is 220 r / min, the carbonization temperature is 1150° C., the holding time is 6 h, and the heating rate is 2.5° C. / min;
[0055] (5) The carbonized material is subjected to secondary screening to obtain an artificial graphite negative electrode material, wherein the sieving mesh number used in the secondary screening is 325 meshes, and the particle size D50 of the artificial graphite negative electrode material is 15.0±2.0 μm.
[0056] Example 2
[0057] This embodiment is a production process for reducing the magnetic content of artificial graphite negative electrode materials, including the steps of:
[0058] (1) graphitizing needle coke in a nitrogen atmosphere to obtain a graphitized product at a graphitization temperature of 2900° C. for 48 hours;
[0059] (2) The graphitized product is first deagglomerated in a toothed roller crusher to a particle size of ≤3.5 mm, and then mixed in a batch mixer and sieved to obtain graphitized particles, wherein the speed of the batch mixer is 180 r / min, the mixing time is 110 min, the mesh size used for sieving is 400 mesh, and the particle size D50 of the graphitized particles is 10.0±2.0 μm;
[0060] (3) The graphitized particles are sequentially subjected to magnetic separation in a first demagnetizer and a second demagnetizer to obtain demagnetized materials, wherein the magnetic induction intensity of the first demagnetizer is 18,000 Gauss, and the demagnetization time is 110 seconds; the magnetic induction intensity of the second demagnetizer is 25,000 Gauss, and the magnetic separation time is 100 seconds;
[0061] (4) kneading the demagnetized material and asphalt in a kneader and then carbonizing them in a tunnel furnace to obtain a carbonized material, wherein the kneading temperature is 20° C., the time is 120 min, the speed of the kneader is 150 r / min, the carbonization temperature is 1150° C., the holding time is 6 h, and the heating rate is 2.5° C. / min;
[0062] (5) The carbonized material is subjected to secondary screening to obtain an artificial graphite negative electrode material, wherein the sieving mesh number used in the secondary screening is 425 mesh, and the particle size D50 of the artificial graphite negative electrode material is 11±2.0 μm.
[0063] Example 3
[0064] This embodiment is a production process for reducing the magnetic content of artificial graphite negative electrode materials, including the steps of:
[0065] (1) graphitizing needle coke in a nitrogen atmosphere to obtain a graphitized product at a graphitization temperature of 3000° C. for 45 h;
[0066] (2) The graphitized product is first deagglomerated in a toothed roller crusher to a particle size of ≤2.0 mm, and then mixed in a batch mixer and sieved to obtain graphitized particles, wherein the speed of the batch mixer is 245 r / min, the mixing time is 70 min, the mesh number used for sieving is 325 mesh, and the particle size D50 of the graphitized particles is 14.0±2.0 μm;
[0067] (3) The graphitized particles are sequentially subjected to magnetic separation in a first demagnetizer and a second demagnetizer to obtain demagnetized material, wherein the magnetic induction intensity of the first demagnetizer is 20,000 Gauss, and the demagnetization time is 120 seconds; the magnetic induction intensity of the second demagnetizer is 30,000 Gauss, and the magnetic separation time is 120 seconds;
[0068] (4) kneading the demagnetized material and asphalt in a kneader and then carbonizing them in a tunnel furnace to obtain a carbonized material, wherein the kneading temperature is 28° C., the time is 120 min, the speed of the kneader is 220 r / min, the carbonization temperature is 1150° C., the holding time is 6 h, and the heating rate is 2.5° C. / min;
[0069] (5) The carbonized material is subjected to secondary screening to obtain an artificial graphite negative electrode material, wherein the sieving mesh number used in the secondary screening is 325 meshes, and the particle size D50 of the artificial graphite negative electrode material is 15.0 um±2.0 μm.
[0070] Example 4
[0071] like Figure 3 As shown, this embodiment is a production process for reducing the magnetic content of artificial graphite negative electrode materials, including the steps of:
[0072] (1) graphitizing needle coke in a nitrogen atmosphere to obtain a graphitized product at a graphitization temperature of 2850° C. for 45 h;
[0073] (2) The graphitized product is first deagglomerated in a toothed roller crusher to a particle size of ≤3.5 mm, and then mixed in a batch mixer and sieved to obtain graphitized particles, wherein the speed of the batch mixer is 220 r / min, the mixing time is 80 min, the mesh number used for sieving is 325 mesh, and the particle size D50 of the graphitized particles is 14.0±2.0 μm;
[0074] (3) The graphitized particles are sequentially subjected to magnetic separation in a first demagnetizer and a second demagnetizer to obtain demagnetized material, wherein the magnetic induction intensity of the first demagnetizer is 20,000 Gauss, and the demagnetization time is 120 seconds; the magnetic induction intensity of the second demagnetizer is 30,000 Gauss, and the magnetic separation time is 120 seconds;
[0075] (4) The demagnetized material and asphalt are first kneaded in a kneader and then carbonized in a tunnel furnace, followed by one depolymerization, one batch mixing, one screening and one magnetic separation to obtain a carbonized material, wherein the kneading temperature is 20° C., the time is 120 min, the kneader speed is 150 r / min, the carbonization temperature is 1150° C., the insulation time is 6 h, the heating rate is 2.5° C. / min, and the one depolymerization, one batch mixing, one screening and one magnetic separation are the same as steps (2) and (3);
[0076] (5) The carbonized material after the first depolymerization, the first batch mixing, the first screening and the first magnetic separation is subjected to a second screening to obtain an artificial graphite negative electrode material, wherein the screening mesh number used in the second screening is 325 meshes, and the particle size D50 of the artificial graphite negative electrode material is 15.0±2.0 μm.
[0077] Comparative Example 1
[0078] like Figure 4 As shown, this comparative example is a production process for reducing the magnetic content of artificial graphite negative electrode materials, comprising the steps of:
[0079] (1) graphitizing needle coke in a nitrogen atmosphere to obtain a graphitized product at a graphitization temperature of 2850° C. for 45 h;
[0080] (2) The graphitized product and asphalt are first kneaded in a kneader and then carbonized in a tunnel furnace to obtain a carbonized material, wherein the kneading temperature is 20°C, the time is 120 min, the speed of the kneader is 150 r / min, the carbonization temperature is 1150°C, the insulation time is 6 h, and the heating rate is 2.5°C / min.
[0081] (3) The carbonized material is first deagglomerated in a toothed roller crusher to a particle size of ≤3.5 mm, and then mixed in a batch mixer and sieved to obtain carbonized material particles, wherein the speed of the batch mixer is 220 r / min, the mixing time is 80 min, the mesh size used for sieving is 325 mesh, and the particle size D50 of the graphitized particles is 14.0±2.0 μm;
[0082] (4) The carbonized material particles are sequentially subjected to magnetic separation in a first demagnetizer and a second demagnetizer to obtain demagnetized material, wherein the magnetic induction intensity of the first demagnetizer is 20,000 Gauss, and the magnetic separation time is 120 seconds; the magnetic induction intensity of the second demagnetizer is 30,000 Gauss, and the demagnetization time is 120 seconds;
[0083] (5) The carbonized material particles are subjected to secondary screening to obtain an artificial graphite negative electrode material, wherein the sieving mesh number used in the secondary screening is 325 meshes, and the particle size D50 of the artificial graphite negative electrode material is 15.0±2.0 μm.
[0084] Comparative Example 2
[0085] This comparative example is a production process for reducing the magnetic content of artificial graphite negative electrode materials, comprising the following steps:
[0086] (1) graphitizing needle coke in a nitrogen atmosphere to obtain a graphitized product at a graphitization temperature of 2850° C. for 45 h;
[0087] (2) The graphitized product is first deagglomerated in a toothed roller crusher to a particle size of ≤3.5 mm, and then mixed in a batch mixer and sieved to obtain graphitized particles, wherein the speed of the batch mixer is 220 r / min, the mixing time is 80 min, the mesh number used for sieving is 325 mesh, and the particle size D50 of the graphitized particles is 14.0±2.0 μm;
[0088] (3) The graphitized particles are sequentially subjected to magnetic separation in a first demagnetizer and a second demagnetizer to obtain demagnetized material, wherein the magnetic induction intensity of the first demagnetizer is 6000 Gauss, and the demagnetization time is 120 seconds; the magnetic induction intensity of the second demagnetizer is 6000 Gauss, and the magnetic separation time is 120 seconds;
[0089] (4) kneading the demagnetized material and asphalt in a kneader and then carbonizing them in a tunnel furnace to obtain a carbonized material, wherein the kneading temperature is 20° C., the time is 120 min, the speed of the kneader is 150 r / min, the carbonization temperature is 1150° C., the holding time is 6 h, and the heating rate is 2.5° C. / min;
[0090] (5) The carbonized material is subjected to secondary screening to obtain an artificial graphite negative electrode material, wherein the sieving mesh number used in the secondary screening is 325 meshes, and the particle size D50 of the artificial graphite negative electrode material is 15.0±2.0 μm.
[0091] Comparative Example 3
[0092] This comparative example is a production process for reducing the magnetic content of artificial graphite negative electrode materials, comprising the following steps:
[0093] (1) graphitizing needle coke in a nitrogen atmosphere to obtain a graphitized product at a graphitization temperature of 2850° C. for 45 h;
[0094] (2) The graphitized product is first deagglomerated in a toothed roller crusher to a particle size of ≤3.5 mm, and then mixed in a batch mixer and sieved to obtain graphitized particles, wherein the speed of the batch mixer is 220 r / min, the mixing time is 80 min, the mesh number used for sieving is 325 mesh, and the particle size D50 of the graphitized particles is 14.0±2.0 μm;
[0095] (3) The graphitized particles are sequentially subjected to magnetic separation in a first demagnetizer and a second demagnetizer to obtain demagnetized material, wherein the magnetic induction intensity of the first demagnetizer is 30,000 Gauss, and the demagnetization time is 120 seconds; the magnetic induction intensity of the second demagnetizer is 20,000 Gauss, and the magnetic separation time is 120 seconds;
[0096] (4) kneading the demagnetized material and asphalt in a kneader and then carbonizing them in a tunnel furnace to obtain a carbonized material, wherein the kneading temperature is 20° C., the time is 120 min, the speed of the kneader is 150 r / min, the carbonization temperature is 1150° C., the holding time is 6 h, and the heating rate is 2.5° C. / min;
[0097] (5) The carbonized material is subjected to secondary screening to obtain an artificial graphite negative electrode material, wherein the sieving mesh number used in the secondary screening is 325 meshes, and the particle size D50 of the artificial graphite negative electrode material is 15.0±2.0 μm.
[0098] Comparative Example 4
[0099] This comparative example is a production process for reducing the magnetic content of artificial graphite negative electrode materials, comprising the following steps:
[0100] (1) graphitizing needle coke in a nitrogen atmosphere to obtain a graphitized product at a graphitization temperature of 2700° C. for 45 h;
[0101] (2) The graphitized product is first deagglomerated in a toothed roller crusher to a particle size of ≤3.5 mm, and then mixed in a batch mixer and sieved to obtain graphitized particles, wherein the speed of the batch mixer is 220 r / min, the mixing time is 80 min, the mesh number used for sieving is 325 mesh, and the particle size D50 of the graphitized particles is 14.0±2.0 μm;
[0102] (3) The graphitized particles are sequentially subjected to magnetic separation in a first demagnetizer and a second demagnetizer to obtain demagnetized material, wherein the magnetic induction intensity of the first demagnetizer is 20,000 Gauss, and the demagnetization time is 120 seconds; the magnetic induction intensity of the second demagnetizer is 30,000 Gauss, and the magnetic separation time is 120 seconds;
[0103] (4) kneading the demagnetized material and asphalt in a kneader and then carbonizing them in a tunnel furnace to obtain a carbonized material, wherein the kneading temperature is 20° C., the time is 120 min, the speed of the kneader is 150 r / min, the carbonization temperature is 1150° C., the holding time is 6 h, and the heating rate is 2.5° C. / min;
[0104] (5) The carbonized material is subjected to secondary screening to obtain an artificial graphite negative electrode material, wherein the sieving mesh number used in the secondary screening is 325 meshes, and the particle size D50 of the artificial graphite negative electrode material is 15.0±2.0 μm.
[0105] The magnetic content of the graphitized products and carbonized materials in the production process of Examples 1 to 4 and Comparative Examples 1 to 4 was measured. The method for testing the magnetic content is as follows. The test results are shown in Table 1.
[0106] Magnetic material content test method: Use a permanent magnetic bar with a magnetic induction intensity of 6000 Gauss to 7000 Gauss to stir and adsorb the magnetic material in the material and pour it into a polytetrafluoroethylene tube; add 8 ml of aqua regia (3:1) to the polytetrafluoroethylene tube to dissolve it; cover the polytetrafluoroethylene tube with a cap and place it in a water bath at 90±5℃ and heat it for 30 minutes; take out the polytetrafluoroethylene tube and cool it to room temperature; use ICP to perform trace analysis of the magnetic material content.
[0107] Table 1 Magnetic content of graphitized products, demagnetizing materials and negative electrode materials in Examples 1 to 4 and Comparative Examples 1 to 4
[0108]
[0109] From the data in the table, it can be seen that the magnetic content of the artificial graphite negative electrode material prepared by the production process of the present invention is less than 3ppm. From the comparison between Example 1 and Example 4, it can be seen that the magnetic content of the artificial graphite negative electrode material can be further reduced by performing depolymerization, batch mixing, screening and magnetic separation again after carbonization.
[0110] Furthermore, by comparing Comparative Example 1 with Example 1 and Example 4, it can be seen that if magnetic separation is not performed before carbonization, the magnetic content of the obtained artificial graphite negative electrode material is much higher than that of the artificial graphite negative electrode material that is magnetically separated before carbonization. By comparing Comparative Example 2 with Example 1, it can be seen that when the magnetic induction intensity of the demagnetizer is the same as the magnetic induction intensity of the magnetic content detection, the demagnetizer cannot adsorb magnetic materials with weaker magnetism, so the demagnetization effect is poor. By comparing Comparative Example 3 with Example 1, it can be seen that when the magnetic induction intensity of the first demagnetizer is greater than the magnetic induction intensity of the second demagnetizer, the demagnetization effect is reduced. By comparing Comparative Example 4 with Example 1, it can be seen that when the graphitization temperature is lower than 2800°C, the magnetic substance contained in the artificial graphite precursor cannot be completely vaporized, thereby increasing the magnetic content of the demagnetizer and the artificial graphite negative electrode material.
[0111] According to the above review, the present invention can gasify magnetic substances such as iron, chromium, nickel, zinc, copper, and cobalt in the artificial graphite precursor by graphitizing the artificial graphite precursor under an inert atmosphere and a temperature of 2800°C or above, and can effectively prevent the magnetic substances from reacting with oxygen to generate other impurities, thereby improving the purity of the artificial graphite and reducing the influence of excessive magnetic content on subsequent electrochemical performance. In addition, the present invention depolymerizes, mixes, screens, and magnetically separates the graphitized product before carbonization, which can effectively prevent the artificial graphite precursor from being completely gasified during the graphitization process due to the fact that some magnetic substances are wrapped inside the graphitized product, and the magnetic content increases due to the fact that the magnetic substances change from weak magnetic to strong magnetic due to the influence of factors such as oxygen during the carbonization process. In the present invention, by setting the magnetic induction intensity of the first demagnetizer and the second demagnetizer to be greater than the magnetic induction intensity of the magnetic object detection during magnetic separation, the weak magnetism that cannot be removed during the magnetic object detection can be effectively removed, and the magnetic induction intensity of the first demagnetizer is further made smaller than the magnetic induction intensity of the second demagnetizer, so that the magnetic objects with different magnetic strengths can be effectively removed in layers, thereby improving the magnetic separation efficiency. Therefore, the production process of the present invention can effectively reduce the magnetic content of the artificial graphite negative electrode material, and an artificial graphite negative electrode material with a magnetic content of less than 3ppm can be obtained without multiple magnetic separations. On this basis, depolymerization, mixed batches, screening and magnetic separation after carbonization can further reduce the magnetic content of the obtained artificial graphite to meet the different needs of different products.
[0112] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A production process for reducing the magnetic content of artificial graphite negative electrode materials, characterized in that: Includes steps: (1) graphitizing an artificial graphite precursor in an inert atmosphere to obtain a graphitized product, wherein the graphitization temperature is 2800° C. or above; (2) deagglomerating, batch mixing and screening the graphitized product to obtain graphitized particles; (3) The graphitized particles are sequentially subjected to magnetic separation in a first demagnetizer and a second demagnetizer to obtain demagnetized material, wherein the magnetic induction intensity of the first demagnetizer and the second demagnetizer is greater than the magnetic induction intensity of the magnetic object detection and the magnetic induction intensity of the first demagnetizer is less than the magnetic induction intensity of the second demagnetizer; (4) kneading the demagnetizing material and a binder and then carbonizing them to obtain a carbonized material; (5) The carbonized material is subjected to secondary screening to obtain an artificial graphite negative electrode material.
2. The production process for reducing the magnetic content of artificial graphite negative electrode materials according to claim 1, characterized in that: The artificial graphite precursor is selected from at least one of anthracite, needle coke, petroleum coke and asphalt, and the magnetic substance in the artificial graphite precursor includes at least one of iron, chromium, nickel, zinc, copper and cobalt.
3. The production process for reducing the magnetic content of artificial graphite negative electrode materials according to claim 1, characterized in that: The inert atmosphere is selected from at least one of nitrogen, helium and argon. The graphitization temperature is 2800° C. to 3100° C., and the time is 45 h to 58 h.
4. The production process for reducing the magnetic content of artificial graphite negative electrode materials according to claim 1, characterized in that: The depolymerization is carried out in a crusher, the rotation speed of the crusher is 900r / min~1400r / min, the particle size of the graphitized product after the depolymerization is 0.002mm~5mm and 95% and above can pass through a 325-mesh sieve, the batch mixing is carried out in a batch mixing machine, the batch mixing time is 60min~120min, the rotation speed of the batch mixing machine is 150r / min~300r / min, and the screening mesh number used in the screening is 200 mesh~500 mesh.
5. The production process for reducing the magnetic content of artificial graphite negative electrode materials according to claim 1, characterized in that: The magnetic field strength of the magnetic object detection is 6000 gauss to 7000 gauss, the magnetic induction strength of the first demagnetizer is 15,000 gauss to 20,000 gauss, and the magnetic induction strength of the second demagnetizer is 25,000 gauss to 30,000 gauss.
6. The production process for reducing the magnetic content of artificial graphite negative electrode materials according to claim 1, characterized in that: The demagnetization time of the first demagnetizer and the demagnetization time of the second demagnetizer are each independently 60s to 150s, the feeding time of the first demagnetizer and the feeding time of the second demagnetizer are each independently 200s to 500s, the slag discharge time of the first demagnetizer and the slag discharge time of the second demagnetizer are each independently 200s to 500s.
7. The production process for reducing the magnetic content of artificial graphite negative electrode materials according to claim 1, characterized in that: The binder is selected from at least one of asphalt and resin, and the kneading is carried out in a kneader. The kneading temperature is 20°C to 40°C, the time is 90min to 150min, the rotation speed of the kneader is 100r / min to 300r / min, the carbonization temperature is 1100°C to 1200°C, the heating rate is 2°C / min to 3°C / min, and the insulation time is 5h-8h.
8. The production process for reducing the magnetic content of artificial graphite negative electrode materials according to claim 1, characterized in that: In step (4), after the carbonization, the steps of deagglomeration, batch mixing, screening and magnetic separation are sequentially included.
9. The production process for reducing the magnetic substance content of artificial graphite negative electrode material according to claim 1, characterized in that: The secondary screening uses a screening mesh number of 200 to 500 meshes.
10. The artificial graphite negative electrode material produced by the production process for reducing the magnetic substance content of the artificial graphite negative electrode material according to any one of claims 1 to 9, characterized in that: The magnetic content is less than or equal to 3ppm.